Patients' satisfaction with anesthesia in enzymatic debridement from a surgical perspective. Issue 5 (August 2020) - Schiefer, J.L.; Lipensky, A.; Fuchs, P.C.; Heitzmann, W.; Schulz, A.
Highlights: Enzymatic debridement is beneficial for the treatment of partial thickness to deep dermal burns. Only little has been published on suitable anesthesia techniques for enzymatic debridement. From a surgical perspective, enzymatic debridement does not necessarily need to be performed under general anesthesia. By the use of these less burdensome techniques for anesthesia, side effects of general anesthesia can be reduced. Furthermore, treatment costs can be decreased and operation room capacity can be saved. Abstract: Introduction: Various clinical studies found that enzymatic debridement (EDNX) is superior to tangential excision after severe burns. The current study evaluates patients' satisfaction with pain management in EDNX with special respect to different anesthesia techniques. Methods: Between 2015 and 2016, all patients at a department of plastic surgery were asked to complete a German-wide validated pain questionnaire. In a retrospective study design, satisfaction with pain management was compared between the control group (diagnosis from the whole field of plastic surgery except burns) and the EDNX group (burns treated with EDNX only). Analgosedation, general, regional and local anesthesia were chosen for pain management. Results: In the control group 403 patients (153 females, 250 males, medium age 53 years) could be included The EDNX group included 88 patients (20 females, 68 males, medium age 38 years). The mean burn size was 5.3% TBSA. Between 0.5%–10.5% of the surface was treated with EDNX. EDNX patients could be treated under analgosedation and regional anesthesia, by topical anesthesia creme and without any anesthesia. They reported less pain during stress (p = 0.04) and were less frequently affected by motion (p = 0.024) and nausea (<0.001). However, they felt that they need more information about alternative anesthetic treatments (<0.001). Conclusion: EDNX can be performed sufficiently either under analgosedation, regional or local anesthesia. Thus, side effects of general anesthesia can be reduced and treatment costs can be decreased. However, it was found that neither after topical anesthetic creme nor after hand block pain treatment was sufficient.